2001
DOI: 10.1016/s0006-3495(01)76265-0
|View full text |Cite
|
Sign up to set email alerts
|

Homo-FRET Microscopy in Living Cells to Measure Monomer-Dimer Transition of GFP-Tagged Proteins

Abstract: Fluorescence anisotropy decay microscopy was used to determine, in individual living cells, the spatial monomer-dimer distribution of proteins, as exemplified by herpes simplex virus thymidine kinase (TK) fused to green fluorescent protein (GFP). Accordingly, the fluorescence anisotropy dynamics of two fusion proteins (TK27GFP and TK366GFP) was recorded in the confocal mode by ultra-sensitive time-correlated single-photon counting. This provided a measurement of the rotational time of these proteins, which, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 33 publications
10
179
0
Order By: Relevance
“…The rotational correlation time ( ) is the time constant of this slow anisotropy decay component and serves as a measure of molecular rotation (25). This value was similar to rotational correlation times measured for GFP (23,28). The two-photon limiting anisotropy of V␣(1-315) (the anisotropy at t ϭ 0) was found to be 0.48.…”
Section: Catalytic Domains Are Arranged As Pairs In the Intact Autoinsupporting
confidence: 67%
See 1 more Smart Citation
“…The rotational correlation time ( ) is the time constant of this slow anisotropy decay component and serves as a measure of molecular rotation (25). This value was similar to rotational correlation times measured for GFP (23,28). The two-photon limiting anisotropy of V␣(1-315) (the anisotropy at t ϭ 0) was found to be 0.48.…”
Section: Catalytic Domains Are Arranged As Pairs In the Intact Autoinsupporting
confidence: 67%
“…A FRET approach seemed reasonable because it has already been shown that tagging the N and C termini of CaMKII␣ with FPs did not alter catalytic activity or the ability of the kinase to form holoenzymes (18), thus FPs attached to either the catalytic or association domains of CaMKII␣ could be used to decipher the structure of the holoenzyme. We specifically chose time-resolved fluorescence anisotropy as the method to measure emFRET because in addition to measuring the proximity between fluorophores, this method can also estimate the number of FPs participating in energy migration and measure the molecular rotation of an FP when attached to CaMKII␣ (22,23).…”
Section: Catalytic Domains Are Arranged As Pairs In the Intact Autoinmentioning
confidence: 99%
“…FRET can also be detected by fluorescence anisotropy (Runnels and Scarlata 1995;Gautier et al 2001;Clayton et al 2002;Lidke et al 2003) which uses linearly polarized light to detect the orientation of the molecules. When there is no energy transfer, the orientation of excited molecule is highly correlated with the orientation of the emitting molecule.…”
Section: Fö Rster Resonance Energy Transfer (Fret)mentioning
confidence: 99%
“…Another method to get a single-color biosensor to perform multiplex could be based on homo-FRET measured by anisotropy [55,56]. HomoFRET occurs when a fluorophore transfers its energy to a closely identical fluorophore.…”
Section: New Methodological Insights For Multiplexing Kinase Biosensorsmentioning
confidence: 99%